FAKTOR RISIKO KERACUNAN PESTISIDA PADA PETANI HORTIKULTURA DI KABUPATEN LAMPUNG BARAT - Yushananta, Prayudhy; Melinda, Nia; Mahendra, Arif; Ahyanti, Mei; Anggraini, Yetti (Poltekkes Kemenkes Tanjung Karang, 2020)
Pesticide poisoning is still an important health problem in agricultural areas, especially horticultural agriculture. Various chronic health effects can be caused by long-term exposure to pesticides. This study aims to determine the risk factor of pesticide poisoning in horticultural farmers in West Lampung Regency.The study used a cross sectional design which was conducted in four different areas as the center of horticulture agriculture, West Lampung Regency, Lampung Province. The study involved 289 participants by interviewing, observing and examining blood samples to measure cholinesterase levels as an indicator of pesticide poisoning. In this section, we have applied research ethical procedures. The obtained data were analyzed using Chi squre test, Odds Ratio test and Logistic Regression.The results showed that the risk factors for pesticide poisoning were incomplete use of personal protected equipment (PPE), spraying with the wrong dose and spraying frequency. Unwearing a complete PPE had a 4.54 times (OR = 4.54; 95% CI 2.09-9.83) higher risk of experiencing pesticide poisoning, and statistically suggested, a very significant relationship (p = 0.0001). While the use of excessive dosage has a risk of 4.39 times (OR = 4.39; 95% CI 1.87-10.33; p = 0.001); and the frequency of spraying more than twice a week had a 2.33 times higher risk of experiencing pesticide poisoning (OR = 2.33; 95% CI 1.24-4.40; p = 0.009).Excessive use of pesticide dosage and the frequency of spraying with the cover blanked method are the main factors of pesticide exposure to farmers. On the other hand, the use of PPE is a method of protection from exposure. It needs joint efforts through increasing knowledge about the dangers of pesticides, pesticide management, how to work safely, and the use of PPE.